COMPARISON OF VARIOUS SPECTRAL INDICES FOR ESTIMATING MANGROVE COVERS USING PLANETSCOPE DATA: A CASE STUDY IN XUAN THUY NATIONAL PARK, NAM DINH PROVINCE - Hai Hoa, Nguyen (Journal of Forestry Science and Technology, 2017)
Using remote sensing and GIS technology to quantify the extents of land covers and detect their changes, in particular mangrove covers, is very important to identify drivers of change, thus providing a good scientific foundation for better management of mangroves in Xuan Thuy National Park, Nam Dinh province. In this study, eight vegetation indices were used, namely SR, NDVI, GNDVI, BNDVI, TV, SAVI, OSAVI and EVI, to quantify the extents of mangrove covers is adopted. As a result, all vegetation indices are reliable for classifying and mapping land covers, greater than 80% of accuracies, in particular OSAVI is the most accurate in comparison with other indices, more than 90% of mapping accuracy as using Planet Scope (3 m x 3 m). Regarding changes in mangrove covers, using 2016 and 2017 PlanetScope data for detecting the change, it has been evidenced with a slight increase of mangroves with 75 ha established. The main drivers of increase of mangrove extents are due to effective mangrove rehabilitation and restoration programs. These findings imply thatmangrove mangement in Xuan Thuy National Park is in a good place.